Cover Image, Volume 10, Issue 2. Issue 2 (14th February 2019) - Beckerle, Philipp; Castellini, Claudio; Lenggenhager, Bigna
Abstract : The cover image is based on the Focus Article Robotic interfaces for cognitive psychology and embodiment research: a research roadmap, by Philipp Beckerle, Claudio Castellini, and Bigna Lenggenhager, https://doi.org/10.1002/wcs.1486 . Abstract : The cover image is based on the Focus Article Robotic interfaces for cognitive psychology and embodiment research: a research roadmap, by Philipp Beckerle, Claudio Castellini, and Bigna Lenggenhager, https://doi.org/10.1002/wcs.1486 .